Success analysis of Fair & Lovely Men salon activation plan: compare & contrast between theories and competitive agencies - Ghosh, Deepa (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.